IMPLEMETASI MAHASISWA MAGANG DALAM MENDUKUNG PELAYANAN PUBLIK DI DINAS SOSIAL, PEMBERDAYAAN PEREMPUAN, DAN PERLINDUNGAN ANAK KABUPATEN BENGKAYANG - Fakundus Theo; Farnsiskus Benno; Eligia Monixa Salfarini (Jurnal Pengabdian Bukit Pengharapan, 2026)
A type of education that provides students with the opportunity to apply their academic knowledge in the workplace. It serves as a means for students to directly understand the implementation of public services focused on social protection, women, and children. The purpose of this article is to describe the implementation of student internships in public service delivery at the Bengkayang Regency Social and Empowerment and Child Protection Agency (DINSOSPPPA). The method used was a direct participatory approach, including observation, participatory mentoring, and observation during the internship. The results of the activities indicate that students contributed to office administration, data and archive analysis, information dissemination to the public, activity report preparation, and support for social program implementation. The curriculum not only helps increase employee productivity but also provides practical experience that enhances professional competence, communication, teamwork, and understanding of public services. The curriculum serves as a continuous link between universities and government institutions in efforts to improve the quality of human resources and services to the general public. The curriculum plays a crucial role as a bridge between the educational and professional worlds and as a way for students to contribute to the development of effective and responsive public services.